Effect of an Educational Program Based on the Health Belief Model on Preventive Behaviors of Urinary Tract Infection among Women - fereshte Javaheri Tehrani; soghra Nikpour (Zanjan University of Medical Sciences and Health Services, 2013)
Background and Objectives : According to the role of the health behaviors in preventing diseases, the present study was conducted to investigate the effect of an educational program based on the Health Belief Model on preventive behaviors of the urinary tract infection among women.   Material and Methods : In this quasi-experimental study, 170 women with history of the urinary tract infection referred to four hospitals in Tehran were selected via convenience sampling method. The participants were allocated to the intervention and control groups. The intervention group received the educational program. Data were gathered using a self-structured questionnaire including demographic characteristics and items on the health behaviors related to the urinary tract infection at baseline and 12 weeks after the intervention. The validity and reliability of the questionnaire was evaluated using the expert panel opinions (r=0.81), and the Cronbachchr('39')s alpha test (α=0.93.). Data were analyzed using the Man Whitney test, Chi-Squared test, and the Wilcox on test. The P<0.05 was considered as the significance level.   Results : There were no significant differences between the two groups at baseline regarding the health behavior scores. Comparison of the mean scores of the total health behaviors and five subgroups showed significant differences between the intervention and control groups after the intervention (P<0.001). There was no significant difference in the score of the treatment regimen adherence (P=0.07).   Conclusion : According to the positive effect of this program designed based on the Health Belief Model this program can be used in order to prevent urinary tract infections among women.